Central Banking in Latin America : The Way Forward - Carriere-Swallow, Yan (IMF Working Papers; Working Paper ;, 2016)
Latin America's central banks have made substantial progress towards delivering an environment of price stability that is supportive of sustainable economic growth. We review these achievements, and discuss remaining challenges facing central banking in the region. Where inflation remains high and volatile, achieving durable price stability will require making central banks more independent. Where inflation targeting regimes are well-established, remaining challenges surround assessments of economic slack, the communication of monetary policy, and clarifying the role of the exchange rate. Finally, macroprudential policies must be coordinated with existing objectives, and care taken to preserve the primacy of price stability.